Hospital‐acquired complications: the relative importance of hospital‐ and patient‐related factors. Issue 5 (30th December 2021) - Duke, Graeme J; Moran, John L; Bersten, Andrew D; Bihari, Shailesh; Roodenburg, Owen; Karnon, Jonathan; Hirth, Steven; Hakendorf, Paul; Santamaria, John D
Abstract: Objective: To quantify the prevalence of hospital‐acquired complications; to determine the relative influence of patient‐ and hospital‐related factors on complication rates. Design, participants: Retrospective analysis of administrative data (Integrated South Australian Activity Collection; Victorian Admitted Episodes Dataset) for multiple‐day acute care episodes for adults in public hospitals. Setting: Thirty‐eight major public hospitals in South Australia and Victoria, 2015–2018. Main outcome measures: Hospital‐acquired complication rates, overall and by complication class, by hospital and hospital type (tertiary referral, major metropolitan service, major regional service); variance in rates (intra‐class correlation coefficient, ICC) at the patient, hospital, and hospital type levels as surrogate measures of their influence on rates. Results: Of 1 558 978 public hospital episodes (10 029 918 bed‐days), 151 486 included a total of 214 286 hospital‐acquired complications (9.72 [95% CI, 9.67–9.77] events per 100 episodes; 2.14 [95% CI, 2.13–2.15] events per 100 bed‐days). Complication rates were highest in tertiary referral hospitals (12.7 [95% CI, 12.6–12.8] events per 100 episodes) and for episodes including intensive care components (37.1 [95% CI, 36.7–37.4] events per 100 episodes). For all complication classes, inter‐hospital variation was determined more by patient factors (overall ICC, 0.55; 95% CI, 0.53–0.57) than by hospital factors (ICC, 0.04; 95% CI, 0.02–0.07) or hospital type (ICC, 0.01; 95% CI, 0.001–0.03). Conclusions: Hospital‐acquired complications were recorded for 9.7% of hospital episodes, but patient‐related factors played a greater role in determining their prevalence than the treating hospital.